Exploration vs. Exploitation: An Empirical Test of the Ambidexterity Hypothesis - He, Zi-Lin; Wong, Poh-Kam (Organization Science, 2004)
While exploration and exploitation represent two fundamentally different approaches to organizational learning, recent literature has increasingly indicated the need for firms to achieve a balance between the two. This balanced view is embedded in the concept of ambidextrous organizations. However, there is little direct evidence of the positive effect of ambidexterity on firm performance. This paper seeks to test the ambidexterity hypothesis by examining how exploration and exploitation can jointly influence firm performance in the context of firms' approach to technological innovation. Based on a sample of 206 manufacturing firms, we find evidence consistent with the ambidexterity hypothesis by showing that (1) the interaction between explorative and exploitative innovation strategies is positively related to sales growth rate, and (2) the relative imbalance between explorative and exploitative innovation strategies is negatively related to sales growth rate.